An art novel for the age of mechanical reproduction: Blaise Cendrars's Dan Yack - Shingler, Katherine (Oxford University Press, 2013)
This article considers Blaise Cendrars's novel Dan Yack (1929) as a variation on the art novel genre, arguing that it rewrites and adapts well-worn art narratives — most notably various iterations of the Pygmalion myth — in order to question the nature and function of art in the age of mechanical reproduction. The first part of the novel investigates traditional art forms, especially sculpture, and describes the failure of the sculptor Sabakoff to attain the Pygmalionesque dream of divine creative power. The second part apparently advances the mechanical art forms of sound recording and cinema as alternative modes of representation more responsive to modern experience; but these too are seen to fail to breathe life into the work of art, producing no more than a sterile imitation of reality and, in the case of cinema, endlessly rehashing past narratives. This pessimism about art is also brought out through the novel's intertexts, which insist on the dangers and limits of artistic creation. Drawing on Walter Benjamin, the article suggests that this pessimism may be tempered somewhat (though certainly not eliminated), since Cendrars's text itself provides a model of an art that works to make the impoverished experience of modern life meaningful by relating it to tradition.